2019
DOI: 10.1186/s12864-019-6340-7
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome variations of Panaxnotoginseng roots treated with different forms of nitrogen fertilizers

Abstract: BackgroundThe sensitivity of plants to ammonia is a worldwide problem that limits crop production. Excessive use of ammonium as the sole nitrogen source results in morphological and physiological disorders, and retarded plant growth.ResultsIn this study we found that the root growth of Panax notoginseng was inhibited when only adding ammonium nitrogen fertilizer, but the supplement of nitrate fertilizer recovered the integrity, activity and growth of root. Twelve RNA-seq profiles in four sample groups were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…This result was consistent with the results such as wheat, cotton, and Camptotheca acuminate [15,36,37]. With the increase of N application rate, root and total N, P, and K accumulation first increased and then decreased, meaning it was possible that excessive N fertilizer would poison the roots of P. bournei seedlings and reduce the ability to absorb nutrients, resulting in N, P, K accumulation decrease [38,39]. With the increase of N application rate, leaves N and P allocation rate first decreased and then increased (opposition to root and stem), indicating that low-medium level N fertilization is more beneficial to root and stem growth, and high-level N fertilization is more beneficial to leaves growth.…”
Section: Effect Of N Fertilizer On Nutrients Accumulation and Allocation In P Bournei Seedlingssupporting
confidence: 90%
“…This result was consistent with the results such as wheat, cotton, and Camptotheca acuminate [15,36,37]. With the increase of N application rate, root and total N, P, and K accumulation first increased and then decreased, meaning it was possible that excessive N fertilizer would poison the roots of P. bournei seedlings and reduce the ability to absorb nutrients, resulting in N, P, K accumulation decrease [38,39]. With the increase of N application rate, leaves N and P allocation rate first decreased and then increased (opposition to root and stem), indicating that low-medium level N fertilization is more beneficial to root and stem growth, and high-level N fertilization is more beneficial to leaves growth.…”
Section: Effect Of N Fertilizer On Nutrients Accumulation and Allocation In P Bournei Seedlingssupporting
confidence: 90%
“…During N assimilation in plants, the NH 4 + is incorporated into amino acids with the action of NH 4 + assimilation enzymes including glutamine synthetase (GS), glutamate synthase (GOGAT) and glutamate dehydrogenase (GDH), and then converted into protein. 9 , 18 , 36 In a previous work, we found that NO 3 − addition increased the activity of GS, GOGAT and GDH under NH 4 + toxicity. 21 Therefore, we measured protein content of wheat roots under different N treatments.…”
Section: Discussionmentioning
confidence: 89%
“… 17 It was found that nitrate alleviated the toxic effect of NH 4 + on root growth of Panax notoginseng by up-regulation of ACLA-3 (encoding ATP-citrate lyase A-3) and several key metabolites in the tricarboxylic acid (TCA) cycle. 18 SLAH3, a slow-type NO 3 − efflux channel, mediates the NO 3 − efflux to buffer the low cellular pH caused by NH 4 + uptake. 6 SnRK1.1 can regulate SLAH3 and thereby mediate NO 3 − efflux, leading to alleviation of high-NH 4 + /low-pH stress.…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous study, the 3-year P. notoginseng seedlings can grow normally in 5 mM ammonium solution, but were inhibited in 15 mM ammonium ( Ou et al, 2019 ). Thus, the concentration of N in the hydroponic was adopted 5 mM.…”
Section: Methodsmentioning
confidence: 99%